Building literacy to build confidence - Hill, Colton Blaine (Kansas State University, 2023)
The goal of my lessons is to help my students analyze and store sound patterns in their minds so they are able to learn and perform music at their highest potential and ultimately gain confidence in themselves through a communal activity they enjoy. We spend time in warmups singing patterns and scales on solfege to build an aural library/model that I assess their ability to recognize/notate when played or sung. I also spend time daily practicing sight singing skills, and I assess them as a whole group (in-person) and individually (online recordings). Students were also asked to create short sight-reading passages for their peers with online software so that they could show their understanding of notating pitch and rhythms. It is my goal to be ever evolving as I find new knowledge and form new connections to the craft of teaching and to the students in my care. Throughout my time with Kansas State University, I have grown to want my students to have a deeper understanding of music literacy and vocal production. This has manifested as teaching more students in small groups and individual settings, when possible, as to focus on each of their instruments with care and attention, and in the way that I approach rhythmic and melodic content in sight reading examples and our performance literature. I have become more aware of the fact that all too often in music education there are performance requirements we expect from our young musicians although we have not adequately taken the time to instruct the basic components of being a confident and versatile musician. Through repetition of sound patterns, isolation and focus on rhythmic patterns, and the teaching of basic vocal production, I have seen growth in more of my students this year that I have in years past. As I move forward, my goal it to be more methodical from the beginning of a student’s time in my classroom/choir program.
Keywords: Music; Literacy; Sight read; Confidence